Triplet Harvesting with a Simple Aromatic Carbonyl. Issue 17 (28th August 2017) - Torres Ziegenbein, Christian; Fröbel, Sascha; Glöß, Maria; Nobuyasu, Roberto S.; Data, Przemyslaw; Monkman, Andrew; Gilch, Peter
Abstract: The front cover artwork is provided by the groups of Prof. Peter Gilch (HHU Düsseldorf) and Prof. Andrew Monkman (Durham University). The image shows a chimera illuminated by the fluorescence emission of thioxanthone, the aromatic carbonyl studied here. Due to singlet and triplet excitations in close energetic vicinity, its photophysics exhibits a chimeric behavior. This behavior renders the class of molecules interesting as emitters in OLEDs. Read the full text of the article at10.1002/cphc.201700683 . Abstract : "Thioxanthone—a simple aromatic carbonyl—acts as triplet harvester. Energy transfer from a triplet sensitizer causes thioxanthone fluorescence giving the compounds potential for OLED applications …" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201700683 .